Extremely low risk for acquisition of a respiratory viral infection in the emergency room of a large pediatric hospital during the winter season. Issue 1 (16th March 2012) - Maltezou, Helena C.; Mougkou, Katerina; Asimaki, Hara; Koniaraki, Katerina; Katerelos, Panos; Giannaki, Maria; Theodoridou, Maria
<x xml:space="preserve">Abstract</x> Please cite this paper as: Maltezou et al. (2012). Extremely low risk for acquisition of a respiratory viral infection in the emergency room of a large pediatric hospital during the winter season. Influenza and Other Respiratory Viruses DOI: 10.1111/j.1750‐2659.2012.00355.x. The aim of this study was to investigate the rate of transmission of respiratory viral infections to children visiting the emergency room of a large pediatric hospital during winter. A total of 615 children were prospectively studied. Twenty‐two (3·6%) children developed at least one symptom compatible with a respiratory viral infection within 1–7 days after the visit, including cough (12 children), fever (8), rhinorrhea (7), and/or respiratory distress (1). Three children (0·49%) developed an influenza‐like illness. These findings indicate that transmission of respiratory viral infections to children visiting an emergency room during the winter season is extremely low.